Release of phosphorus from thermal conversion of phosphorus-rich biomass chars – Evidence for carbothermic reduction of phosphates. (1st June 2023) - Lidman Olsson, Emil O.; Schmid, Daniel; Karlström, Oskar; Enemark-Rasmussen, Kasper; Leion, Henrik; Li, Songgeng; Glarborg, Peter; Dam-Johansen, Kim; Wu, Hao
Highlights: Release of ash-forming elements in different conditions quantified. Phosphorus is released due to carbothermic reduction reactions in char. Association of phosphorus in char important for release. Phosphorus and potassium release correlate positively with lower oxygen availability. Formation of stable species may explain residual phosphorus in char. Abstract: Biomass can be used to generate heat, power, or biofuels in thermal conversion processes such as combustion, gasification and pyrolysis. However, some types of biomass contain high levels of phosphorus, which can be released to the gas phase and cause operational or environmental problems. The mechanism(s) responsible for phosphorus release has not been convincingly established. Understanding the high-temperature phosphorus chemistry is also important in order to enable efficient recovery of phosphorus in residues from thermal conversion of biomass. In this work, the release of phosphorus from wheat bran char and sunflower seed char in different gas environments (100 % N2, 1–20 % O2, and 10 % CO2 ) and temperatures (900–1100 °C) was studied. The chars were converted in a horizontal tube reactor and characterized using ICP-OES, XRD, SEM-EDS, and 31 P NMR. The release of ash-forming elements was determined using ICP-OES analysis of the char and sample residues, whereas the release of carbon was determined using CO and CO2 gas analysis. In both chars, phosphorus was present primarily together with potassium and magnesium, mainly as pyrophosphates in the wheat bran char, and largely as orthophosphates in the sunflower seed char. For wheat bran char, the release of phosphorus increased from 27 % at 900 °C to 71 % at 1100 °C in N2, whereas the release was at least 20 % lower in the oxidizing atmospheres (1–20 % O2, or 10 % CO2 ). The sunflower seed char reached a maximum release of 55 % at 1100 °C in N2 . For wheat bran char, the molar ratio of released carbon/phosphorus was close to 2.5, which fits well with the theoretical value for carbothermic reduction of phosphates (P2 O5 (s, l) + 5C(s) → P2 (g) + 5CO(g)). At 1100 °C, in N2, the release of phosphorus, potassium and sodium occurred mainly during the first 10 min. It was shown that KMgPO4, used as a model compound, could be reduced by carbon starting from 950 °C, but that some of the phosphorus remained in the condensed phase. The work provides a better understanding of phosphorus release and presents evidence showing that carbothermic reduction reactions can be an important phosphorus release mechanism for seed- and grain-based biomass char.